Causes of irreversible blindness in the Mettapracharak (Watraikhing) Eye Center among the elderly between 2010 and 2016 - ยิ่งยง, เพ็ญพิมล (วารสารสถาบันราชสุดาเพื่อการวิจัยและพัฒนาคนพิการ, 2020)
This cross sectional study aims to evaluate the causes of irreversible blindness among This cross sectional study aims to evaluate the causes of irreversible blindness among the elderly in the Mettapracharak (Watraikhing) hospital between 2010 and 2016. The sample of the study were new eye outpatients attending the hospital between 2010 and 2016. The participants aged more than 60 years old with irreversible legal blindness in accordance with the World Health Organization criteria (best corrected visual acuity less than 3/60 or visual field less than 10 degree in the better eye despite all medical and surgical interventions. The statistics used were frequency, percentage, mean and standard deviation. The results of the study showed 8483 patients to be recruited, 5183 (61.1%) were females and 3300 (38.9%) were males. 1281 (15.1%) had legal blindness. 230 (18.0 %) were bilateral blindness. Main causes of visual loss were as follows: 220 (17.2%) glaucoma, 214 (16.7%) diabetic retinopathy, 183 (14.3%) age-related macular degeneration, 78 (6.1%) ocular vascular occlusion, 54 (4.2%) retinitis pigmentosa, 35 (2.7%) optic atrophy, 15 (1.2%) amblyopia, 150 (11.7%) combination of causes, 113 (8.8%) corneal disorder and others 219 (17.1%). The most commom cause of irreversible blindness among the elderly was glaucoma, diabetic retinopathy and age-related macular degeneration respectively. Policy Recommendation is to know the cause of irreversible legal blindness that can Policy Recommendation is to know the cause of irreversible legal blindness that can initiate the government and eye care specialists in promoting more suitable strategies for the better awareness of these avoidable complications.